The Efficacy of Night Bracing in the Treatment of Adolescent İdiopathic Scoliosis: A Systematic Review - Çolak, Tuğba Kuru; Dereli, Elif Elçin; Akçay, Burçin; APTİ, ADNAN; Maeso, Santiago Lasa (MDPI, 2024)
Background/Objectives: The effectiveness of night braces alone or in combination with other treatments for adolescent idiopathic scoliosis remains unclear. This systematic review study aimed to review and analyze the available literature to determine whether night braces are an effective treatment for idiopathic scoliosis. Methods: A total of 162 databases, including Cochrane Library (reviews, protocols, trials), Web of Science, PubMed, Medline, Scopus, PEDro, CINAHL (EBSCO), Ovid and Google Scholar, were searched for published articles from inception to February 2024. The available literature was screened by the following terms: "scoliosis and night-time brace", "scoliosis and night brace", "scoliosis and part-time bracing", "scoliosis and Providence" and "scoliosis and Charleston". Results: Twenty studies were included; only one study was a randomized controlled trial, and most of the studies were retrospectively designed. Providence, Charleston and Boston braces were used as night braces. The Cobb angle was evaluated in all studies, and Cobb angle change after treatment and surgical treatment rates were the parameters that were evaluated the most. In one study, the angle of trunk rotation, quality of life, perception of spinal appearance, and physical activity level were measured. In one study, sagittal plane assessments were performed in addition to the Cobb angle. Conclusions: The results of this review suggest that there is no evidence to support the use of night braces in the treatment of adolescent idiopathic scoliosis. Randomized controlled trials with a well-designed methodology are needed to determine the efficacy of night braces.
Keywords: Adolescent; Brace; Scoliosis; Spine